Content Marketing and E-WOM Strategies on TikTok to Increase Motorcycle Sales at Honda TDM Pramuka Dealership. - Hati, Lintang Adelia Mustika; Asnusa, Soraya (Manunggal Halim Jaya, 2025)
This study aims to analyze the impact of content marketing strategies and Electronic Word of Mouth (E-WOM) on TikTok in boosting motorcycle sales at Honda TDM Pramuka dealerships. With over a billion active users, TikTok offers companies a significant opportunity to engage directly with consumers through creative and interactive content. A quantitative approach was employed, utilizing surveys and digital content analysis to assess the effectiveness of various marketing strategies, such as promotional videos, user reviews, and interactive challenges. Additionally, the study examines the role of E-WOM in building consumer trust and influencing purchasing decisions. The results indicate that content marketing strategies, particularly promotional videos and interactive challenges, can increase user engagement and stimulate buying interest. Reviews and testimonials from TikTok users also play a crucial role in fostering trust, ultimately driving motorcycle sales at Honda dealerships. The study concludes that combining an effective content marketing strategy with strong E-WOM is a powerful marketing tool for increasing sales and enhancing consumer loyalty in the digital era.